A comparative braking scheme in auto-electric drive systems with permanent magnet synchronous machine - Crescent Onyebuchi Omeje; Candidus Ugwuoke Eya (International Journal of Applied Power Engineering (IJAPE), 2022)
Permanent magnet synchronous machines (PMSMs) are gaining popularity due to renewable energy and the electrification of transportation. Permanent magnet synchronous machines are receiving interest because to their great dependability, low maintenance costs, and high-power density. This research compares surface mounted permanent magnet (SMPM) with interior permanent magnet (IPM) synchronous machines using MATLAB. Mathematical models and simulation analyses of two permanent magnet synchronous machines under regenerative braking are presented. Maximum regeneration power point (MRPP) and torque (MRPP-torque) for two machine types were simulated at variable electrical speed and q-axis current. Simulation results showed IPMSM produced more output power due to saliency than SMPM at varying speed and current with higher MRPP and MRPP-Torque. Simulation was used to compare the dynamic impacts of constant and variable braking torques on an auto-electric drive's speed and produced torque on a plain surface and a sloppy driving plane. 81.68% and 74.95% braking efficiency were measured on level ground and a sloppy plane, respectively. Simulations indicated that lithium-ion battery state of charge varied linearly with constant braking torque and exponentially with varying braking torque, reflecting efficiency values. All simulations were in MATLAB/Simulink 2014.